Optimizing the Role of the Master of Ceremony in Hybrid Events: Strategic Approaches for Effective Communication - Annisa, Nur Annisa Khoiriyah; Moh Muslimin; Agus Baihaqi (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
In the digital era, hybrid events are an innovative solution in combining two elements, namely physical and virtual audiences. This research aims to analyze the role of MC in maximizing audience engagement through effective communication strategies. Using a qualitative descriptive approach with a case study design at several hybrid events. Data collection through observation, interviews and documentation. The research results show that the MC has a very strategic role as the main key in an event. Challenges faced by MC include technical obstacles, involvement of both audiences, and sudden changes to the event schedule. The strategies used to create effective communication include inclusive communication, improvising, two-way interaction, appropriate time management, and the use of nonverbal communication which have proven effective in creating a more interactive and inclusive event atmosphere. This research provides practical guidance and enriches the literature. However, limitations in case coverage and research methods indicate the need for further studies with a more comprehensive approach for more representative results.